Can we predict severe reactions during peanut challenges in children?. Issue 6 (31st July 2013) - van Erp, Francine C.; Knulst, André C.; Kentie, Petra A.; Pasmans, Suzanne. G. M.; van der Ent, Cornelis K.; Meijer, Yolanda
Abstract: Background: Limited and contrasting data are available about risk factors for severe reactions during double‐blind, placebo‐controlled food challenge (DBPCFC). Knowing these risk factors would help to improve safety precautions and choosing the best setting for challenge. We assessed whether we could determine predictors for positive and severe food challenge outcome (FCO) with regular available patient data in children suspected for peanut allergy. Methods: A retrospective study in children referred for DBPCFC with peanut was performed during a 3‐year period. Reactions during challenge were classified as mild/moderate (Sampson's grade 1–3) and severe (Sampson's grade 4–5). We performed uni‐ and multivariable logistic regression to determine predictors for positive and severe FCO. Results: A group of 225 children with a median age of 6.7 (IQR 5.0–9.5) years were studied. In 109 (48%) children, food challenge outcome was positive and 24 (11%) children developed a severe reaction. The level of sIgE for peanut OR 1.14 (1.08–1.20), male gender OR 0.40 (0.20–0.81), having another food allergy OR 0.43 (0.20–0.88), were independently related to positive FCO. No significant differences were found between children with severe and non‐severe FCO with respect to age, gender, asthma, sIgE, or previous reaction to peanut. Conclusions: Although predictors of positive FCO could be identified, none of the studied risk factors could predict a severe reaction during peanut challenge. When challenging a child sensitized to peanut, clinicians should be prepared and equipped to handle any reaction in all cases.